Occupational risk for personnel working in veterinary clinics through exposure to vectors of rickettsial pathogens - Escárcega, Angélica (2019)
Workers at veterinary clinics are exposed to zoonotic pathogens, which, though infrequently, can lead to serious consequences. The aim of the present study was to estimate the seroprevalence for rickettsial pathogens in veterinary clinic personnel in Ciudad Juárez, Chihuahua, Mexico. Voluntary participants included 106 veterinarians, 19 pet groomers, 36 veterinary assistants and 6 administrative workers who supplied blood samples taken by venipuncture. Detection of Rickettsia rickettsii, Ehrlichia spp. and Anaplasma phagocytophilum was conducted by indirect immunofluorescence assay (IFA) and polymerase chain reaction (PCR) techniques. To determine risk factors for the seroprevalence, the study considered social, demographic and occupational variables as well as the clinical signs and symptoms of the participants. Logistic regression procedures were performed, and the odds ratio (OR) was calculated with confidence intervals corresponding to a probability of 95%. The results indicate that 54% of the participants had a positive seroreaction to at least one of the pathogens evaluated and 2% were positive to all. The coexposure was as follows: 3% to R. rickettsii and A. phagocytophilum, 9% to Ehrlichia spp. and A. phagocytophilum, and 2% to Ehrlichia spp. and R. rickettsii. It was established that grooming posed the highest risk for R. rickettsii exposure. The implementation of appropriate management practices for zoonotic diseases is recommended to avoid health problems that may be life threatening to personnel in veterinary clinics.